Addition of climate variables to ZMD's gridded climate datasets - International Research Institute for Climate and Society (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
ZMD’s ENACTS datasets were updated and now include the following variables: Precipitation (daily), Precipitation (decadal), Maximum Temperature, Minimum Temperature, Mean Relative Humidity, Surface Pressure, Pressure Reduced at Mean Sea Level, Solar Radiation, Wind Speed at 10 meters, Reference evapotranspiration using FAO Penman-Monteith equation.